Development of algorithm for single axis sun tracking system - Yi, L.Z. (American Institute of Physics Inc., 2016)
The output power from a solar panel depends on the amount of sunlight that is intercepted by the photovoltaic (PV) solar panel. The value of solar irradiance varies due to the change of position of sun and the local meteorological conditions. This causes the output power of a PV based solar electricity generating system (SEGS) to fluctuate as well. In this paper, the focus is on the integration of solar tracking system with performance analyzer system through the development of an algorithm for optimizing the performance of SEGS. The proposed algorithm displays real-time processed data that would enable users to understand the trend of the SEGS output for maintenance prediction and optimization purposes. Â© 2016 Author(s).